Recovery dynamics of wetland vegetation along a hydrological gradient in an agriculturally used inland valley in Uganda - Kai Behn; Miguel Alvarez; Samuel Mutebi; Mathias Becker (Wetlands Ecology and Management, 2024)
Wetlands in East Africa are important for providing ecosystem services and for conserving biodiversity. They are also suitable and increasingly used for agriculture. Between cropping cycles, spontaneous vegetation regrows on fallow plots. We hypothesize that recovery is affected by hydro-edaphic conditions and the duration of the fallow period. Land use intensification reduces fallow durations. A multi-year field study investigated the dynamics, biodiversity, and potential uses of fallow vegetation species after a disturbance event in an inland valley wetland in Central Uganda. The wetland was stratified into three hydrological positions along a gradient comprising the valley fringe, the mid-valley, and the riparian zone. In each zone, biomass was removed, and the soil was tilled, simulating a common disturbance event. Subsequently, four plots of 4 × 4 m size were delineated in each zone. Vegetation regrowth was subsequently monitored over a period of two years. We recorded and analyzed changes in aboveground live biomass, abundance of selected plant species, taxonomic and functional composition, and evenness during a 27-months recovery phase. While annual species dominated the vegetation initially, these were gradually replaced by herbaceous perennials, and eventually by tall reeds and woody plants, constituting three successional stages. The dynamics were similar, but species composition differed across the positions. At all successional stages, we observed the presence of useful wild plants, but also invasive species such as Mimosa pigra were recorded. While temporary fallows are important for biodiversity in tropical wetlands, such successions cannot substitute for the functions and services provided by natural vegetation and may promote invasive species.